2015
DOI: 10.5492/wjccm.v4.i3.159
|View full text |Cite
|
Sign up to set email alerts
|

Opening the doors of the intensive care unit to cancer patients: A current perspective

Abstract: The introduction of new treatments for cancer and advances in the intensive care of critically ill cancer patients has improved the prognosis and survival. In recent years, the classical intensive care unit (ICU) admission comorbidity criteria used for this group of patients have been discouraged since the risk factors for death that have been studied, mainly the number and severity of organic failures, allow us to understand the determinants of the prognosis inside the ICU. However, the availability of intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…Nevertheless, studies published in recent years have demonstrated similar mortality rates to noncancer ICU patients. The better survival results are attributed to advances in ICU care and better access in this population to critical care [ 15 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies published in recent years have demonstrated similar mortality rates to noncancer ICU patients. The better survival results are attributed to advances in ICU care and better access in this population to critical care [ 15 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 As outcomes in patients with cancer continue to improve, these assumptions may not be valid. 5 A systematic review illustrated that variations in ICU mortality among patients with cancer were largely attributable to differences between study populations’ severity of illness, type of admission, performance status, and need for organ support rather than the presence of cancer. 6 …”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Physicians in intensive care units (ICUs) are more inclined to consider admitting critically ill patients with cancer worldwide. 3 , 4 One recent population-based study that used a cancer registry database in the United Kingdom reported that approximately 5% of patients with solid tumors required an ICU admission within 2 years of cancer diagnosis. 5 Another multicenter study in Europe found that nearly 1 in 7 patients admitted to ICUs had a malignant neoplasm.…”
Section: Introductionmentioning
confidence: 99%